Personality traits and customer-oriented behavior of the Malaysian nurses - Ping, L. L. (Medwell Journals, 2016)
The purpose of this study is to examine the relationship between personality traits and customer-oriented behavior among nurses in the selected public hospitals in Malaysia. The respondents consisted of female and male nurses with majority of them were staff nurses. A quantitative, cross sectional survey method was used in this study. Factor analysis and multiple regression analysis were employed to analyze the data collected. The findings of this study revealed that personality traits (i.e., extraversion and agreeableness) were positively related to customer-oriented behaviour. Agreeableness made the strongest influence in explaining the variance of customer-oriented behavior. This study provides theoretical and managerial implications by using the concept of customer-oriented behavior in enhancing nurses' job performance in the hospitals.